Yield and proximate composition of Pleurotus florida cultivated on wheat straw supplemented with perennial grasses - PRASAD, SHALINEE; RATHORE, HIMANSHI; SHARMA, SATYAWATI; TIWARI, GARIMA (The Indian Journal of Agricultural Sciences, 2023)
Pleurotus spp. are the most commonly cultivated and consumed mushrooms in India. This mushroom grows on almost all kinds of traditional as well as the non-traditional biomass sources giving good yield. In the present study, Panicum virgatum and Panicum maximum grasses were utilized for the cultivation of Pleurotus florida. The highest biological efficiency was obtained in case of 50% WS + 50% PM (68.45%) followed by the 100% WS (66.43%). The harvested fruiting bodies analysed for the nutritional parameters revealed that significant difference was found among the fruiting bodies produced on the selected agrowastes studied for the different proximates analyzed especially in protein content. Based on the biological efficiency of the substrates tested, utilization of Panicum maximum biomass seems to be a promising supplement with wheat straw for growing P. florida.